The Role of Business Process Reengineering (BPR) in Reducing Costs - Mohammad Yasin Al Rahahleh (Journal of Accounting, Business and Management (JABM), 2010)
This study aimed at describing the impact and role of re-engineering processes in reducing costs of production, of the production process and post-production, and their impact on decisions made on cost. The descriptive analytical approach was followed. Data was collected through a questionnaire that measures the concept of re-engineering processes and the relationship of its application to reducing costs. The studys population incorporated 100 companies that participated in the, Award of King Abdullah II Center for Excellence. The study found that the use of re-engineering processes brings down the costs of inputs and the production process and the costs of post-production process. This eventually reduces overall costs, though not to a large degree. This method has had radical changes on the companies that apply re-engineering in all aspects of technical, economic, administrative and accounting aspects and that exclude unnecessary activities. The study recommends that companies adopt the re-engineering approach because of its benefits, especially in reducing the costs, which in turn leads to further benefits. It should be handled form the accounting perspective, which requires the development of accounting systems to attain the required benefits.